2011
DOI: 10.1302/0301-620x.93b9.26873
|View full text |Cite
|
Sign up to set email alerts
|

Does body mass index affect clinical outcome post-operatively and at five years after primary unilateral total hip replacement performed for osteoarthritis?

Abstract: Studies describing the effect of body mass index (BMI) on the outcome of total hip replacement have been inconclusive and contradictory. We examined the effect of BMI on medium-term outcome in a cohort of 1617 patients who underwent a primary total hip replacement for osteoarthritis. These patients were followed prospectively for five years with the outcomes of dislocation, revision, duration of surgery and deep and superficial infection studied, as well as collecting Harris hip scores (HHS) and Short-Form 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 23 publications
(18 reference statements)
7
80
0
Order By: Relevance
“…There is disagreement regarding whether these individuals have greater surgical risks and costs for the episode of care [2,4,6,10] and the magnitude of those risks and costs. Further, there is no established threshold for obesity as defined by BMI in defining increased complications and risks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is disagreement regarding whether these individuals have greater surgical risks and costs for the episode of care [2,4,6,10] and the magnitude of those risks and costs. Further, there is no established threshold for obesity as defined by BMI in defining increased complications and risks.…”
Section: Discussionmentioning
confidence: 99%
“…Michalka et al [18] reported on operative time, blood loss, suboptimal implant placement, the surgeons' perception of operative difficulty, and the six-minute walk test. Davis et al [6] studied dislocation, revision, duration of surgery, and deep and superficial infections. Both groups concluded total hip replacement ''should not be withheld'' or that ''obese patients gain similar benefit''.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When obesity is defined as a body mass index (BMI) greater than 30 kg/m 2 in adults, obesity is recognized as an independent risk factor for postoperative hip dislocation in several studies [2,6,8,15,18,22,28,35]. However, in these patients with obesity, it is not known whether the risk is only in the early postoperative period or if the risk persists several years after surgery.…”
Section: Introductionmentioning
confidence: 99%